Analysis on the matching performance of thermal expansion valve with plate evaporator - 谷波; 景步云; 黎远光 (Zhileng xuebao)
The capacity matching and system's stability are two important aspect for the matching of thermal expansion valve with plate evaporator.The optimizing matching of TEV and PE can enlarge the refrigerating capacity,lower down the system noise,and benefit to the system running stability as well as raise the precision of system control.